Interest of para-aortic lymphadenectomy for locally advanced cervical cancer in the era of PET scanning. (May 2022) - Khebbeb, Sirine; Rathat, Gauthier; Serrand, Chris; Bourdon, Aurélie; Ferrer, Catherine; Duraes, Martha
Highlights: Para-aortic lymphadenectomy is recommended in the case of negative para-aortic positron emission tomography-computed tomography (PET-CT) due to its low morbidity. The major finding of this study was a false-negative rate of 9.5% when pelvic PET-CT was positive. Surgical staging can be discussed regardless of pelvic status if the patient presents a high surgical risk. Abstract: Background and objectives: Treatment of locally advanced cervical cancer (LACC) involves pelvic chemoradiotherapy, using an extended field in the case of para-aortic involvement. 18-Fluoro-D-glucose positron emission tomography combined with computer tomography (PET-CT) is an accurate method for the detection of metastatic nodes. The objective of this study was to evaluate the performance of PET-CT for lymph node staging of LACC. Methods: This bicentric retrospective study included patients with LACC who had a PET-CT scan followed by para-aortic lymphadenectomy between January 2015 and December 2019. Based on pathological findings, sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV) and false-negative (FN) rates of PET-CT for para-aortic node involvement were evaluated. Results: Seventy-one patients who had undergone laparoscopic lymphadenectomy were included in this study. The intraoperative complication rate was 2.8%. Sensitivity, specificity, NPV and PPV for PET-CT were 55% [95% confidence interval (CI) 44.6–67.1], 84% (95% CI 75–92), 93% (95% CI 87–99) and 33% (95% CI 22–44), respectively. FN rates in the case of negative or positive pelvic PET-CT were 5.7% and 9.5%, respectively. Conclusions: Para-aortic lymphadenectomy is recommended for lymph node staging in the case of negative para-aortic PET-CT. In view of the low FN rate of PET-CT, surgical staging should be discussed regardless of pelvic status if the patient presents high surgical risk, or if this delays the commencement of chemoradiotherapy.